The Strength of Freight Wagon in the Past and Present (Current Problems in Rail Vehicles, 2021)
The paper deals with the issue of dimensioning of railway freight wagon car bodies. The current state of regulations and their real application is analysed. The requirements in the regulations are confronted with the knowledge gained during tests and assessment of an operational strength failures of freight wagon. Suggestions for changing of existing standards are given.
Keywords: freight car; sizing requirements; fatigue failures; regulations